Zapisz w jak najprostszej postaci OBLICZENIA NIE SAME WYNIKI !!!
RÓBCIE TO TAK np. (a+b)-(2a-b)-(a-2b)=a+b-2a+b-a+2b= -2a+4b
Najpierw trzeba usunac nawiasy !!!
a) 3(2x-1)+4(1-x)
b)2(7x+5)-6(x-2)
c)-2x(8-x)-5(x kwadrat +3x)
d)5(3-2x)-4x+6)*3

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-16T18:58:28+01:00
A) 3(2x-1)+4(1-x)=6x-3+4-4x=2x+1
b)2(7x+5)-6(x-2)=14x+10-6x+12=8x+22
c)-2x(8-x)-5(x kwadrat +3x)=-16x+2xkwadrat-5xkwadrat-15x=-3xkwadrat+x
d)5(3-2x)-4x+6)*3=15-10x-12x-18=-22x-3
2010-02-16T19:05:17+01:00
A) 6x-3+4-4x=2x+1
b) 14x+10-6x+12=8x+22
c) -16x+2x-5x(kwadrat)-15x=-34x-5x(kwadrat)
d) 15-10x-12x+18=33-22x